Pengaruh Pelaksanaan Program Kelas Ibu Hamil terhadap Pengetahuan Ibu Tentang Manfaat ANC di Desa Mekar Sari Kecamatan Delitua Kabupaten Deliserdang Tahun 2023 - Rio jenita Sipayung (Lembaga Pengembangan Kinerja Dosen, 2023)
The implementation of the class program for pregnant women is one program that is a means to increase knowledge for pregnant women, this program is a form of classroom learning. This affects ANC visits that should be done by pregnant women every month. This visit not only affects the mother but also on the health of the fetus being conceived. This implementation is not only for learning about getting pregnant, but learning about labor, childbirth and family planning. Thus it is highly recommended for pregnant women to take a class program for pregnant women to increase knowledge to mothers. The purpose of this study is to know the knowledge of mothers about the benefits of ANC in Mekar Sari Village Kecamatan Delitua Kabupaten Deliserdang. The research design used in this study was A One Pretest-Posttest Design with total sampling technique. The results of this study indicate that there is an influence on the implementation of the class program of pregnant women on the knowledge of mothers about the benefits of ANC from the results of significance 0.000<0.005.